"Not so immediate" hypersensitivity–the danger of biphasic anaphylactic reactions. Issue 4 (July 1998) - Brazil, E; MacNamara, A F
Abstract : OBJECTIVE: To assess how commonly clinically significant biphasic anaphylactic reactions occur after apparently successful treatment of an anaphylactic reaction. Cases were analysed to determine whether there were any markers that would allow early identification of patients who would subsequently develop a biphasic response. METHOD: Retrospective review of case notes of 34 patients admitted for observation after an anaphylactic reaction that had required treatment with adrenaline. RESULTS: Six patients (18%) had biphasic reactions. No clinical features on initial presentation identified those likely to have a biphasic response. These patients however required significantly more adrenaline to ameliorate their initial symptoms (p = 0.03) compared with those having a simple uniphasic reaction. CONCLUSIONS: Biphasic anaphylactic reactions occur frequently. There are no clinical features that allow identification of patients likely to have a biphasic response. These patients require higher doses of adrenaline to control their initial symptoms and this should be considered a marker for patients who may develop a biphasic response. These results confirm that all patients being discharged after treatment for an acute anaphylactic reaction must be made aware of the risk of a second phase response after apparent clinical resolution.